Генетичний аналіз авротики (ААВВТТ) за ознакою наявність воскової осуги - Шпильчин, В.В.; Мартиненко, В.С.; Терновська, Т.К. (Фактори експериментальної еволюції організмів, 2014)
Aims. The aim of our work is to identify genotypes of the three morphotypes of genome-substituted Aurotica amphidiploids, which demonstrate permanent variation by the genes controlling the glaucousness trait. Methods. Genetic analysis through crossing and assessment of segregating populations. PCR of genome DNA of alternative genotypes. Results. Haplotypes of contrasting morphotypes based on glaucousness trait: Aurotica green iw3 W1 iw1 Iw2(T) Iw3(T), Aurotica green-blue iw3 W1 iw1 iw2(T) Iw3(T), Aurotica blue iw3 W1 iw1 iw2(T) iw3(T). Based on the results of SSR analysis Iw2 is one of the segregated genes, which is located on T genome, not on B genome. Conclusions. Contrasting Aurotica morphotypes differ by one mutation Іw2(Т)→iw2(Т) (green – blue Aurotica) or two, the second mutation is Іw3(Т)→iw3(Т) (green – green-blue Aurotica).

Key words: glaucousness, microsatellite, amphidiploids.